A Self-Mixing Laser Sensor Design With an Extended Kalman Filter for Optimal Online Structural Analysis and Damping Evaluation - Bes, C.; Belloeil, V.; Plantier, G.; Gourinat, Y.; Bosch, T. (IEEE/ASME transactions on mechatronics, 2007)
We have developed a new algorithm based on the extended Kalman filter in order to improve the resolution of a self-mixing (SM) optical displacement sensor. This noncontact sensor, which provides vibration measurement with a very high accuracy, can be used for online quality control, for example, measuring the damping of excited mechanical structures. This SM sensor subject to weak feedback has been tested in comparison with a commercial vibrometer in order to measure the frequency response function (FRF) of a plate with a passive damping to be characterized, and to show the efficiency of a damping treatment.